Characteristics and management of hepatotoxicity in hospitalized patients treated with triazoles: a systematic review - da Silva Mamona, Thamara; Oliveira Santos Junior, Genario; Paraná Ferreira Filho, Raymundo; de Moura Santos, Pablo (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2024)
Introduction: Fungal infections are the main causes of morbidity and mortality in immunocompromised and severely hospitalized patients. Triazole antifungal drugs are used on a large scale in the treatment of hospital’s fungal infections and there is concern about their adverse events, particularly hepatotoxicity. Aim: Considering the frequency of triazoles use in hospitalized patients, the aim of this systematic review was to assess the overall certainty of evidence for the hepatotoxicity caused by triazoles in hospitalized patients. Materials and Method: This is a systematic literature review, using the Pubmed/Medline and Scopus databases. Data collection was carried out in July – August 2020 and March – April 2021. The inclusion criteria for the study were: articles in English, Portuguese and Spanish; patients older than 18 years who used triazole antifungals (fluconazole, voriconazole, itraconazole or posaconazole). To characterize hepatotoxicity, criteria established by Hy’s Law were used. Results: We found 71 articles on the occurrence of hepatotoxicity, a total of 1.033 patients. Regarding the indication for the use of triazoles, the main one was invasive fungal diseases (52.7%). The duration of treatment with triazoles ranged from 24 to 53 days. Fluconazole was the drug associated with the greatest severity. Five studies detected mutations in cytochrome P450 CYP3A4 and CYP2C19. Conclusion: There are a considerable number of publications in the literature on hepatotoxicity with triazole antifungals. This review showed that its incidence is higher in the male and young population. Posaconazole and voriconazole had a higher frequency of hepatotoxicity.